ANALISIS PENGEMBANGAN TRADISI SESITIAN SEBAGAI POTENSI WISATA BUDAYA DI DESA ULAK PANDAN KECAMATAN NASAL KABUPATEN KAUR PROPINSI BENGKULU - Fitriyanti, Zeni; Wijayanti, Ayu (JURNAL ILMIAH IDEA, 2025)
This research aims to analyze the development of the Sesitian tradition as a potential cultural tourism in Kaur Regency. The method used is qualitative research with a descriptive approach, where data is collected through observation, interviews, and documentation. This research uses the tourism theory proposed by Bob McKercher, which emphasizes that cultural tourism has a diversity of tourist motivations, different cultural experiences, as well as challenges in cultural preservation and the risk of commodification. The results show that the Sestian tradition has great potential to be developed as a cultural tourism attraction by considering several main factors. First, tourists’ motivations in visiting cultural destinations are very diverse, so a more flexible approach in presenting the Sestian tradition is needed. Secondly, tourists’ level of understanding of culture also varies, so education about this tradition is an important aspect of its development. In addition, this study found that there is a risk of cultural commodification that can reduce the authentic value of the Sestian tradition, so tourism management must consider aspects of sustainability and local community involvement. The conclusion of this study emphasizes the importance of sustainable management strategies, active community involvement, and support from the government in preserving and developing the Sestian tradition as a cultural tourism potential in Kaur Regency.